Cost-effectiveness analysis of nimotuzumab combined with gemcitabine for K-Ras wild type locally advanced or metastatic pancreatic cancer in China - Rong Long; Hao Guo; Kun Chen (Scientific Reports)
Abstract The phase III NOTABLE trial has revealed that nimotuzumab plus gemcitabine achieves greater clinical benefit in the first-line treating K-Ras wild type locally advanced (LA) or metastatic pancreatic cancer (mPC), compared to gemcitabine. Hence, herein, we examined the cost-efficiency of introducing nimotuzumab to gemcitabine, relative to gemcitabinealone, in first-line K-Ras wild type LA or mPC therapy from a Chinese payer perspective. We generated an exhaustive decision-analytical Markov model using three exclusive health states to incorporate both clinical and economic consequences of nimotuzumab plus gemcitabine versus gemcitabine alone as first-line therapy patients with K-Ras wild type LA or mPC. Using a 10-year lifetime horizon, we assessed the total medical expenditure, quality-adjusted life years (QALYs), and incremental cost‒effectiveness ratio (ICER) as the primary surrogate outcomes of our model. Sensitivity analyses were conducted via alteration of internally tweakable parameters, and further subgroup analyses were conducted as needed. The overall health surrogate outcomes were 2.94 QALYs ($215,799) among patients with nimotuzumab plus gemcitabine and 1.83 QALYs ($86,039) among patients with gemcitabine alone (ICER value, $117,263/QALY; Incremental net health benefit [INHB] value, − 2.46/QALY). Based on our sensitivity analysis, among all parameters, progression-free survival (PFS) utility was of utmost importance, and it exerted a considerable impact on our model. The ICER consistently well exceeded the willingness-to-pay (WTP) threshold and negative INHBs were observed across all patient subcategories with zero alteration recorded as cost-effective in the subgroup analyses. Nimotuzumab plus gemcitabine, relative to gemcitabine alone, is not a cost-effective first-line treatment among patients with K-Ras wild type LA or mPC at the current prices offered in China.